Saturday
March 25, 2017

Post a New Question

Posted by on .

log3 2 +log3 X +log3 (2x-3)=log3 X + log3 (x+1) + log3 (x-1) - log3 (x^2-1)

  • precalc - ,

    log3 [ 2x(2x-3) ] = log3[ x(x+1)(x-1)/(x^2 - 1) ]

    "anti-log" it , remember the old "whatever you do to one side, you must do to the other side"

    2x(2x-3) = x(x+1)(x-1)/(x^2 - 1)
    4x^2 - 6x = x
    4x^2 - 7x = 0
    x(4x - 7) = 0
    x = 0 or x = 7/4
    but log x would be undefined if x=0
    so x=7/4

    better check my arithmetic

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question